HUBUNGAN PENGETAHUAN DAN DUKUNGAN KELUARGA DENGAN POLA PANTANG MAKAN PADA IBU NIFAS DI WILAYAH KERJA UPT. PUSKESMAS LENTENG KABUPATEN SUMENEP TAHUN 2016 - Iva Gamar Dian Pratiwi; Mujib Hannan (Wiraraja Medika : Jurnal Kesehatan, 2016)
Indonesia is one country that is developing one of the barriers that frequently   occur   in   any   society   never   eat   after   melahirkan.Berdasarkan preliminary study will be undertaken in the region UPT 2016 against PHC Lanteng 10 puerperal women in puerperal women earn 9 (90%) were abstinence in eating and earn 1 puerperal women (10%) are not eat abstinence. The purpose of this study was to analyze the relationship between knowledge and support families with a pattern of eating abstinence in puerperal women in the work area upt Lanteng health center in 2016.The study design used is an analytical method with cross sectional design. The population in this study as many as 35 large sample puerperal women and 29 for women. Engineering samples are used random sampling. Get data from health centers uptLanteng and questionnaires.The results showed almost half (37.9%) mothers have enough knowledge, almost half (41.3%) mothers have less family support, and most (58.6%) mothers of abstinence from food during puerperium.Statistical research results obtained using the sign test to test the relationship patterns of abstinence knowledge eating in puerperal women obtained value (ρ = 0.003 <α = 0.05) so H0ditolak which means there is a relationship between knowledge of the pattern of eating and abstinence statistical test results with  test  sign  test  the  relationship  with  the  family support  abstinence  eating patterns, obtained values (ρ = 0.007 <α = 0.05) so that H0 is rejected, which means  that  there  is  a  correlation  between  the  patterns  of  family  support  in puerperal women eating abstinence. Enough knowledge and support families who are less special concern that should be handled by the health workers actively conduct outreach to improve nutrition in puerperal women